Tithing programs: pathways for enhancing and improving the health status of the underprivileged - James K. Elrod; John L. Fortenberry (BMC, 2017)
Abstract Background While quick and easy access to healthcare services is a reality for some, others experience significant hardships, even for receipt of the most basic health and medical care and attention. To those who effectively have been shut out of the healthcare marketplace due largely to economic deficiencies, healthcare providers engaged in the delivery of charitable services are a critical lifeline. Myriad attempts by governmental entities to remedy disparate access and shore up the delivery of healthcare services directed toward the disadvantaged have failed to close gaps, warranting pursuit of novel methods that offer potential and the hope that sufficient access might one day become a reality. Discussion One innovative approach for enhancing and improving charitable healthcare endeavors in communities was developed by Willis-Knighton Health System. The initiative, known as the Tithing the Bottom Line program, essentially takes a portion of the health system's earnings and directs these resources to fund pursuits that improve quality of life in the community, with the enhancement of health and wellness services for the underprivileged being a top priority. These resources magnify the efforts of establishments already endeavoring to serve those in need and create powerful synergies which positively impact the health status of disadvantaged populations. To shed light on Willis-Knighton Health System's unique charitable initiative, this article describes its tithing program in detail, supplying operational guidance that will permit healthcare institutions to establish like programs in their communities. Conclusions With healthcare access gaps remaining pronounced despite numerous attempts by governmental entities to realize full access, grassroots efforts remain critical to bolster health and wellness broadly in communities. Deficiencies carry dramatic consequences for both the disadvantaged and the greater communities in which they reside. The synergistic, cooperative effort realized by Willis-Knighton Health System's tithing program offers great potential for reducing healthcare disparities, yielding healthier populations, enhanced opportunities, and better communities.